A comparison of client feedback, global assessment of functioning and academic progression data from a Higher Education Counselling Service's online videoconferencing and in-person counselling. - Titterton, Jane (2015)
Online videoconferencing counselling (OVC) is an innovative and flexible way of providing counselling services particularly to those living in rural areas or concerned about the stigma attached to seeking in-person mental health support and counselling. It is increasingly being offered in higher education institutions to increase access to counselling and psychological services as well as widening participation for students. Research into the field is growing and indicates that the use of online videoconferencing technology in counselling is effective and non-inferior to in-person or face-to-face counselling. The present naturalistic study explored the client feedback, global assessment of functioning and academic progression data for students (n=67) of a London-based higher education institution who received OVC (via Skype video call). These results were compared with those students (n=237) who received in-person counselling. Results indicate non-inferiority in terms of feedback, global assessment of functioning and academic progression. Global assessment of functioning was significantly more improved for the online videoconferencing group compared to the in-person group. Feedback and academic progression was also slightly more positive, though not significantly, for the online videoconferencing group. These results were disseminated in terms of the differences and nuances between online videoconferencing and in-person counselling. These results provide justification for additional research into the therapeutic processes underlying OVC as distinct from in-person counselling. Furthermore, these results lend support for the development of a counselling theoretical model that addresses the unique therapeutic processes that occur during OVC. Additionally, there are implications for undergraduate and postgraduate counselling training programmes to incorporate specific OVC training into their curriculums as well as continuous professional development for those already practicing.